(untitled) (Research, Society and Development, 2021)
This study aimed to demonstrate the scientific productions about the assistance provided to the patient victim of Cranioencephalic Trauma - TBI, especially with regard to nursing and epidemiological data that involve this problem. This is a bibliographic search, carried out from December 2020 to January 2021. The search for scientific articles was carried out in the following databases: Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO). 15 articles were selected to compose the current study between 2016 - 2020, later discussions about the studies were elaborated. By reading the articles, it was possible to identify the importance of initial care for the victim of TBI by the nurse, in addition to the care taken during hospitalization and the applicability of the Glasgow scale in these patients. It is concluded that the application of adequate care reduces the risks and possible damages afterwards to the client victim of TBI.